The Vernacular Matters of American Literature - Lemke, S. author. aut Link
IX, 189 p.
Keywords: From this study of Mark Twain, Zora Neale Hurston, and Ana Castillo arises a new model for analyzing American literature that highlights commonalities - one in which colloquial and lyrical style and content speak out against oppression.